Knowledge Management Mediation Model of Higher Learning Institution Performance - Buafra, Khalid; Nizam Salahudin, Shahrul (International Journal of Sustainable Construction Engineering and Technology, 2022)
There are many studies on Knowledge Management (KM) in different organizations however less investigation on university, especially teaching staff in terms of using KM to enhance their duties at the universities. Thus, this paper presents a study to examine the Critical Influential Factors of Knowledge Management and Innovation Management on UAE Universities Performance. The study adopted a quantitative approach where a questionnaire survey was carried out among academic staffs of UAE universities. A total of 330 respondents involved in this survey. The data gathered from the survey was used to develop the mediation model which comprises of innovation learning acts as mediator to the relationship between the five knowledge management variables and the university performance variable. The model was developed and assessed in SmartPLS software. The mediation model comprises of direct effect relationship and mediation effect relationship. For direct effect relationship, it was found that two KM dimensions have a direct significant effect on universities’ performance, which are knowledge acquisition and knowledge application. And also, it indicates that there is a significant direct effect for innovation learning on university performance. For mediation effect, it was found that innovation learning on the relationship between KM dimensions (knowledge acquisition, knowledge storage, knowledge sharing, and knowledge application) and universities’ performance. The results from this modelling work, indicated that knowledge acquisition and knowledge sharing have a significant indirect effect on universities’ performance with partial mediation for knowledge acquisition and full mediation for knowledge sharing. The findings of this research could benefit academic and decision makers in terms of enhancing organization performance through KM. Also, innovation learning can be considered as a stimulant to KM in further enhancing the university organization performance.